Profile of Akira Tamura: Yokohama city Planner - Tamura, Chichiro (International Planning History Society Proceedings, 2018)
This essay is a profile of Akira Tamura (1926-2010), and an attempt to locate him in the contemporary history of city planning in Japan. In the 1960s Yokohama faced various urban problems accompanying its rapid economic growth. Ichio Asukata, elected in 1963 as the new socialist mayor, tried to solve them through the local government in an era when the central government’s power remained strong. Asukata then met Tamura, who was working for a local planning office, and asked for his assistance. Tamura proposed to Asukata a new concept for Yokohama as Japan’s ‘international management centre’, and the implementation of the Six Spine Projects, including the Minato Mirai 21 development. Asukata decided to invite Tamura to join the city government. Tamura worked for Yokohama city for over a decade, and his planning vision was inherited by the city’s officers. Moreover, his accomplishments have encouraged many planners and officers in other local governments. Tamura later lectured on urban policy at university, authored eleven books, and travelled to educate the public on city planning (or ‘machi-zukuri’). In short, Tamura was a leader and pioneer in the field of city planning as an officer of local government.